2019
DOI: 10.4244/eij-d-19-00282
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery perforation during chronic total occlusion percutaneous coronary intervention: epidemiology, mechanisms, management, and outcomes

Abstract: Aims:The aim of this study was to describe the epidemiology, mechanisms, management, and outcomes of coronary artery perforation during chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Methods and results:We included 1,811 consecutive patients undergoing CTO PCI at five centres between 2011 and 2018. Coronary perforation was observed in n=99 (5.5%). Patients with perforation were older, had a higher J-CTO score, more often required antegrade dissection/re-entry and the retrograde approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 16 publications
(30 reference statements)
0
43
2
1
Order By: Relevance
“…Subintimal tracking and vessel injury seemed to be developed inevitably when management of complex CTO lesion. [21][22][23][24] Some studies showed that extensive subintimal stenting and target vessel injury increased the chance of revascularisation. 24 25 Recent studies evaluated the role of occlusion length on the outcomes of successful CTO PCI, 26 27 however, there are still some questions needed to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…Subintimal tracking and vessel injury seemed to be developed inevitably when management of complex CTO lesion. [21][22][23][24] Some studies showed that extensive subintimal stenting and target vessel injury increased the chance of revascularisation. 24 25 Recent studies evaluated the role of occlusion length on the outcomes of successful CTO PCI, 26 27 however, there are still some questions needed to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published analysis of 1811 cases from five European centres it occurred in 5.5% of the CTO PCIs, with more than half of these cases requiring management and 20% resulting in tamponade. The following characteristics were found to be independently associated with coronary perforation: older age, occlusion length >20 mm, rotational atherectomy, antegrade dissection/re-entry, and use of the retrograde approach [9]. In another multicentre US registry analysing 2097 CTO PCIs performed in 2049 patients, the incidence of perforation was 4.1%, with 14% of the patients developing tamponade requiring pericardiocentesis.…”
Section: Perforationmentioning
confidence: 99%
“…Coronary perforation is the Achilles’ heel of chronic total occlusion (CTO) percutaneous coronary intervention. It occurs in approximately 6% of CTO procedures and is associated with a high risk for periprocedural death ( 1 ). By convention, sealing a coronary perforation requires the deployment of one or more covered-stents (CSs).…”
Section: Introductionmentioning
confidence: 99%